A matter of hand: Causal links between hand dominance, structural organization of fronto-parietal attention networks, and variability in behavioural responses to transcranial magnetic stimulation. (January 2017) - Cazzoli, Dario; Chechlacz, Magdalena
Abstract: Considerable evidence suggests that, on a group level, human visuospatial attention is asymmetrically organized, with a right-hemispheric dominance. The asymmetrical organization of the superior longitudinal fasciculus (SLF) has been shown to account for the right-hemispheric dominance in visual attention. However, such account is by no means universal, and large individual differences in asymmetrical performance on visuospatial tasks have been reported. Furthermore, the variability in the SLF lateralization has been shown to correlate with behavioural asymmetries. Continuous theta burst stimulation (cTBS) enables to temporarily interfere with cortical activity. cTBS applied over the posterior parietal cortex (PPC) has been previously used to systematically study attentional asymmetries. Interestingly, large individual differences in the effectiveness of stimulation have been reported. In accordance with earlier both animal and human studies, one possible cause underlying these striking individual differences might lie in the structural organization of frontoparietal pathways subserving visuospatial attention. Thus, the current study employed diffusion tractography to examine the relationship between the variability in the structural organization of the SLF and the individual differences in attentional shifts induced by a modified cTBS (cTBSmod ; triplets of pulses at 30 Hz, repeated at 6 Hz) applied over the IPS, as measured by a line bisection task. Consistent with previous studies, on a group level, cTBSmod applied over the right intraparietal sulcus (IPS) triggered a rightward bisection bias shift, and there were no significant effects of cTBSmod applied over the left IPS. However, further analyses demonstrated that both handedness and structural variability (as assessed based on hindrance modulated orientational anisotropy) within the middle and the ventral branches of the SLF predicted individual differences in the cTBSmod -induced attentional shifts. Our study thus suggests that the effects of cTBSmod over the IPS may depend on intra-hemispheric interactions between cortical loci controlling visual attention. To conclude, our findings provide converging evidence for the notion put forward previously that inter-individual variability in the structural organization of intra-hemispheric frontoparietal connections has important implications for the functional models of human visual attention. Moreover, we hypothesize that this may also be relevant for the understanding of attentional disorders and their rehabilitation.